Optimal Design of Lining For A Medium-Frequency Induction Furnace - R.R. Rahmanov; Sh.Sh. Kenjaboev; N.M. Saidmakhmadov; N.Kh. Tadjiev; U.O. Yuldashev (Indonesian Journal Publisher, 2026)
This article analyzes the issues of optimal design of the lining for a medium-frequency induction furnace. One of the main problems considered is the wear of the lining, its service life, and the change in its thermal resistance during the melting of ferrous metals and their alloys in induction furnaces. The study examines the selection of optimal lining thickness, the proper organization of gunning (repair) processes, and their impact on production efficiency. In addition, a number of assumptions are introduced for the operational model of the process, and approaches aimed at improving the performance of the lining are proposed. As a result, the importance of lining parameters and maintenance strategies in ensuring the optimal operating conditions of the furnace is substantiated